2022
DOI: 10.1590/1679-78256935
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and In-depth Tensile Mechanism Analysis of Grouted Sleeve Lapping Conectors

Abstract: To study the failure modes, bearing capacity, ductility, and sleeve strain of grouted sleeve lapping connectors, 36 specimens were tested under uniaxial tensile load. The test results show that the sleeves are under longitudinal tension at the beginning, which changes to longitudinal compression in the late stage of loading, and the changing load increases gradually with the lap length. The force transmission path and mechanical mechanism of the connectors are analyzed. The distribution and development process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The stress mechanism of the APC connector under tension was reported prev [23]. The sleeve was under axial tension in the initial stage of loading and axial com sion in the later stage of loading.…”
Section: Stress Analysis Of Connection Under Tensionmentioning
confidence: 93%
See 2 more Smart Citations
“…The stress mechanism of the APC connector under tension was reported prev [23]. The sleeve was under axial tension in the initial stage of loading and axial com sion in the later stage of loading.…”
Section: Stress Analysis Of Connection Under Tensionmentioning
confidence: 93%
“…Outward force of the steel bar Inward force of the sleeve Outward force of the sleeve of the steel bar Comparative tests on the mechanical properties of grouted splice connectors and APC connectors were conducted by Yu et al [24]; it was shown that the constraint on the grouting material of an APC connector was stronger than that of a grouted splice connector, and the mechanical properties of the APC connector were better than those of the grouted splice connector. The APC connectors have mainly been studied using uniaxial tension tests [23,25] to determine the bearing capacity, load-displacement curves, and hoop and longitudinal strains of the sleeves. Meanwhile, the ductility, residual deformation, and hoop and longitudinal strain of the APC connector under high-stress repeated tension and compression loads have largely gone uninvestigated.…”
Section: Inward Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Under the premise of full grouting, the prefabricated concrete beam connected by sleeve grouting can meet the requirements of bearing capacity and ductility. Yu et al [20] carried out tensile tests on 36 joints to study the stress mechanism of steel sleeve grouting lap joints, fitted the formula of joint ultimate bond strength, and proposed the formula of sleeve critical lap length.…”
Section: Introductionmentioning
confidence: 99%